Humanism in Philosophical Studies - Maryati, Yenny (Yayasan Sembilan Pemuda Indonesia, 2024)
The philosophical theory known as humanism emphasizes the value and position of human beings, considering them as the core of everything. This article is created in an effort to provide information in the form of a review of humanism in the study of philosophy from various perspectives of various figures, especially in the realms of religion, education, and social aspects, as well as its development over time. The article is written using the library research method, where the data collection technique involves literature review in journals. The research results show that the humanistic perspective originates from the fundamental belief in humans as creatures with innate and natural characteristics in the Middle Ages. Humanism is an ideology that prioritizes human values. The philosophical theory known as humanism emphasizes the value and position of human beings, considering them as the core of everything. The main focus of humanism is the natural characteristics of humans, their limits, and tendencies. Understanding humanism in philosophical studies plays a crucial role in providing knowledge to discover the essence of life, encouraging thinking towards the search for the essence of science to address significant issues (aporia).